Strategi Branding Bujang Rimba dalam Membentuk Self Image di Media Sosial - Ghea Grahmaulidya; Dedeh Fardiah (UNISBA Press, 2023)
Abstract. This study aims to determine the branding strategy used by Bujang Rimba in forming self-image on Instagram social media @bujangrimba_. This goal is divided into three factors, namely communication strategy, branding consistency and relevance and Bujang Rimba's self-image. This study uses a qualitative approach with case study analysis, the theory used to support this research is the Impression Management Theory from Jones & Pittman. Self-presentation by Bujang Rimba provides added value in building branding and self-image. Case study analysis is considered to be the most effective method for exploring how Bujang Rimba's strategy builds their branding. The results of the research show (1) Bujang Rimba has never formed and promoted as a creative agency, but they are running as they are as a group of people who have the same hobbies and activities, as well as references to the same interests. With the concept of their everyday style that is humorous and